2014
DOI: 10.1371/journal.pone.0090913
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in Luminal Fluid of the Ovine Uterus

Abstract: Microvesicles and exosomes are nanoparticles released from cells and can contain small RNAs, mRNA and proteins that affect cells at distant sites. In sheep, endogenous beta retroviruses (enJSRVs) are expressed in the endometrial epithelia of the uterus and can be transferred to the conceptus trophectoderm. One potential mechanism of enJSRVs transfer from the uterus to the conceptus is via exosomes/microvesicles. Therefore, studies were conducted to evaluate exosomes in the uterine luminal fluid (ULF) of sheep.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
200
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(214 citation statements)
references
References 61 publications
12
200
1
1
Order By: Relevance
“…Of particular interest is the finding of mRNAs and protein for enJSRV, which supports results published by Burns et al (2014). It is known that the conceptus trophectoderm contains enJSRV around day 12 (Dunlap et al 2006) due to the incorporation of viral particles shed from the endometrium (Black et al 2010).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Of particular interest is the finding of mRNAs and protein for enJSRV, which supports results published by Burns et al (2014). It is known that the conceptus trophectoderm contains enJSRV around day 12 (Dunlap et al 2006) due to the incorporation of viral particles shed from the endometrium (Black et al 2010).…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, Racicot et al (2012) demonstrated liberation of exosomes by ovine uterine cells in vitro and described the expression of IFNT-related genes in their cargo. Afterwards, another study described the presence of these microvesicles in ovine uterine flushings recovered from day 14 of the estrous cycle and day 14 of pregnancy (Burns et al 2014). The results presented here are the first to demonstrate that membrane-bound organelles matching features previously described for exosomes (Gyö rgy et al 2011, Vlassov et al 2012 are present in ovine uterine flushings as early as day 10 post-estrus/mating, which provide strong support for a role for exosomes in early events responsible for the onset of IFNT secretion and establishment of pregnancy in ewes.…”
Section: Discussionmentioning
confidence: 99%
“…Uterine luminal fluid (ULF) contains embryotrophic substances, collectively termed histotroph, that drive elongation of the conceptus via effects on trophectoderm proliferation and migration as well as attachment and adhesion to the endometrial luminal epithelium (LE; Gray et al, 2001;Spencer et al, 2008;Bazer et al, 2010;Forde et al, 2014a). The ULF is derived primarily from transport and (or) synthesis and secretion of substances by the endometrial LE and glandular epithelium (GE), but also by the conceptus , and it is a complex and rather undefined mixture of proteins, lipids, amino acids, sugars (glucose, fructose), ions, and exosomes/microvesicles (Bazer, 1975;Gray et al, 2001;Bazer et al, 2012;Burns et al, 2014;Forde et al, 2014b). P4 induces the expression of a number of genes in the endometrial epithelium that are then further stimulated by factors from the conceptus (e.g., IFNT and PGs) and the endometrium itself Brooks et al, 2014;Lonergan and Forde, 2014).…”
Section: Establishment Of Pregnancy In Cattlementioning
confidence: 99%
“…Cellsecreted vesicles containing bioactive molecules such as miRNA, mRNA and proteins have been shown to mediate cell communication among different cell types (BURNS et al, 2014;. Recently, an experiment demonstrated the transfer of cell-secreted vesicles from parthenogenetic embryos to cloned embryos, providing a new paradigm for embryo-to-embryo communication in vitro (SAADELDIN et al, 2014).…”
Section: Epigenetic Mechanisms Of Natural Reprogramming Versus Cloningmentioning
confidence: 99%
“…EXO described in uterine fluid contained miRNA, mRNA and proteins such as CD63 and HSP70 (exosome markers). Different mRNAs were identified in EXO from pregnant and cyclic ewes, among them the endogenous beta retrovirus (enJSRVs), enJSRVs mRNA is produced in the endometrium and is important for throphectoderm differentiation, thus suggesting that EXOs are mediating this process (BURNS et al, 2014).…”
Section: Epigenetic Mechanisms Of Natural Reprogramming Versus Cloningmentioning
confidence: 99%